A Convenient Assay for Estimating the Possible Involvement of Efflux of Fluoroquinolones by Streptococcus pneumoniae and Staphylococcus aureus: Evidence for Diminished Moxifloxacin, Sparfloxacin, and Trovafloxacin Efflux - Beyer, Rebecca (American Society for Microbiology, 2000)
We developed a simplified assay for estimating efflux by measuring the effect of reserpine on the growth of Streptococcus pneumoniae and Staphylococcus aureus over 7 h. Reserpine enhanced ciprofloxacin and levofloxacin 17 to 68%. The hydrophobic drug trovafloxacin and the drug moxifloxacin, with a bulky C-7 substituent but hydrophilicity similar to that of levofloxacin, showed little (0 to 11%) reserpine-enhancing effect. The ease of resistant mutant strain selection correlated with efflux susceptibility.